Relationship between sludge volume index and biomass structure within activated sludge systems - Mesquita, D. P. (2008)
In activated sludge systems, the sludge settling ability is considered a critical step where filamentous bulking and biomass deflocculation are the most common problems, causing the reduction of the effluent quality. Furthermore, in recent years image processing techniques have been successfully used to elucidate the activated sludge morphology. Keeping that in mind, a program was developed for the characterization of activated sludge collected from eight wastewater treatment plants comprising both good and poor settling sludge. The results showed a strong correlation between the sludge volume index, and image analysis based parameters emerging from filamentous and aggregated biomass contents, explaining the state of biological systems.